The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1367-2630/ab60f2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient quantum transport in a multi-site system combining classical noise and quantum baths

Abstract: We study the population dynamics and quantum transport efficiency of a multi-site dissipative system driven by a random telegraph noise (RTN) by using a variational polaron master equation for both linear chain and ring configurations. By using two different environment descriptions-RTN only and a thermal bath+RTN-we show that the presence of the classical noise has a non-trivial role on quantum transport. We observe that there exist large areas of parameter space where the combined bath+RTN influence is clear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 51 publications
(98 reference statements)
0
25
0
Order By: Relevance
“…The present study also builds on the work by Kurt et al [46] that examined the effect of Holstein phonons and the work of Mozafari et al [47] that examined the effect of Peierls phonons on energy transfer through small networks. Our intermediate results for phononfree networks or networks with fixed site positions are consistent with previous observations [44].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The present study also builds on the work by Kurt et al [46] that examined the effect of Holstein phonons and the work of Mozafari et al [47] that examined the effect of Peierls phonons on energy transfer through small networks. Our intermediate results for phononfree networks or networks with fixed site positions are consistent with previous observations [44].…”
Section: Introductionmentioning
confidence: 77%
“…As discussed in the introduction, many theoretical studies based on quantum master equation approaches found that Holstein couplings can accelerate the excitation energy transport compared with the purely coherent cases [23,46,57]. These studies always consider a fixed system Hamiltonian coupled with a Holstein bath.…”
Section: B Network Coupled To Holstein Phononsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the thorough characterisation of decoherence effects in CTQWs is a key ingredient for their use in quantum technology and, in particular, to envisage strategies that may mitigate or cancel out noise. Several studies investigated how noise stemming from the interaction between the system and the environment affects the dynamics of quantum walks [17][18][19][20][21][22][23][24]. Different effects may emerge, such as localization, transition toward a classically distributed walker [20,21,23], but also an improvement in excitation transport efficiency [18,19,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, it has become evident that environmental noise need not be an enemy to the preservation of quantumness [4]. On the contrary, it may sustain the persistence of quantum coherence and, as a consequence, improve the efficiency of quantum transport in complex systems [5][6][7][8][9][10]. In this sense, the initial skepticism on the presence of quantum phenomena in macroscopic "hot and dirty" systems, due to their very short coherence time, has been overcome [11].…”
Section: Introductionmentioning
confidence: 99%